THE FIGURES OF SPEECH OF JOKOWI THE PRESIDENT OF INDONESIA IN THE APEC CEO SUMMIT 2014 IN BEIJING CHINA - Farida Hanum; Dwijani Ratnadewi (Tell : Teaching of English Language and Literature Journal, 2017)
The researcher analyzed figurative language in Jokowi‟s speech by using stylistics and context theory. Theresearcher could analyze Jokowi‟s speech in social community and eventually finding meaning in everyexpression of speech that were appeared. In this study, researcher used the descriptive qualitative to analyze thedata. The researcher approach were stylistics and context teory for analyzing the variety of figurative languagesuch as anaphora, simile, epiphora, anadiplosis, symploce. The researcher used the video and text of Jokowispeech. Some type of figurative language were found in this research. There were meaning in every phrases,repetition of words and emphazing words to find the true meaning. The Jokowi showed that the main purpose ofhis speech was to affect the APEC CEO participantto invest in Indonesia.